Tolerance Tourism: A Historical Perspective on Cultural Integration in Glodok Chinatown Jakarta - Insani, Zsarin Astria Puji; Sendra, I Made; Narottama, Nararya (Bina Nusantara University, 2025)
The research examines the multifaceted history of tolerance tourism in Glodok Chinatown, Jakarta, Indonesia, with a focus on the Peranakan Chinese community and its unique cultural heritage. Glodok's development as a tourism destination is examined through the lens of